Antioxidant and cytotoxic activity of Tecoma stans against lung cancer cell line (A549) - Jayachandran Philip Robinson; Kumaresan Suriya; Ramasamy Subbaiya; Ponnusamy Ponmurugan (Universidade de São Paulo, 2017)
ABSTRACT Human have been constantly using plants and plant products to overcome many diseases. The antioxidant property of the plant sources is studied to obtain an efficacious drug against cancer. The objectives of the present study is to evaluate the antioxidant and cytotoxic activity of the Tecoma stans extracts against lung cancer cell line in comparison with vincristine drug. The antioxidant activity was studied using the standard DPPH assay and the cytotoxic activity using MTT assay. DPPH assay results show that methanolic extract of T. stans in higher concentration show better antioxidant potential than the standard L-ascorbic acid. They exhibited strong antioxidant potential at 20 µg/mL concentration. The absorbance at 517 nm showed that in the range of 0.201-0.0203 compared to that of absorbance of ascorbic acid at 0.023.Cytotoxic activity was studied using MTT assay which showed that the increase in concentration of extract increases the cell death. At 100µg/mL concentration there is an increased cytotoxic activity, i.e., 99% of cell inhibition. The results of antioxidant and anticancerous activity may be positively correlated.